2019
DOI: 10.1177/1534735419850634
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of mHealth Mindfulness Intervention for Cancer Patients and Informal Cancer Caregivers: A Feasibility Study Within an Integrated Health Care Delivery System

Abstract: To assess feasibility and preliminary efficacy of a mobile/online-based (mHealth) mindfulness intervention for cancer patients and their caregivers to reduce distress and improve quality of life (QoL). Material and Methods: Twoarm randomized controlled trial within Kaiser Permanente Northern California targeting cancer patients who received chemotherapy and their informal caregivers. The intervention group received a commercially available mindfulness program for 8 weeks. The wait-list control group received u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
263
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(272 citation statements)
references
References 73 publications
3
263
2
4
Order By: Relevance
“…We identified 17 RCTs ( Willems et al, 2017 ; Mendoza et al, 2017 ; Graetz et al, 2018 ; Ferrante et al, 2018 ; Admiraal et al, 2017 ; Compen et al, 2018 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Greer et al, 2019 ; Ham et al, 2019 ; Ji et al, 2019 ; Kubo et al, 2019 ; Rosen et al, 2018 ; Uhm et al, 2017 ; Urech et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2018 ) and 8 pre-post design studies ( Børøsund et al, 2019 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; McCarroll et al, 2015 ; Pappot et al, 2019 ; Park et al, 2019 ; Pope et al, 2019 ; Trinh et al, 2018 ). Nine studies (5 RCTs and 4 pre-post designs) tested physical activity / rehab / fitness interventions ( Mendoza et al, 2017 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Ji et al, 2019 ; Uhm et al, 2017 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; Park et al, 2019 ; Trinh et al, 2018 ), six studies – CBT interventions (4 RCTs and 2 pre-post designs) ( McCarthy et al, 2018 ; Willems et al, 2017 ; Compen et al, 2018 ; Greer et al, 2019 ; Greer et al, 2019 ; Ham et al, 2019 ; Børøsund et al, 2019 ), three studies - mindfulness/stress management interventions (3 RCTs) ( Kubo et al, 2019 ; Rosen et al, 2018 ; Urech et al, 2018 ), two studies - social support (1 RCT and 1 pre-post design) ( Zhu et al, 2018 ; Pappot et al, 2019 ), two studies - information/psychoeducation (2 RCTs) ( Graetz et al, 2018 ; Admiraal et al, 2017 ), two studies – weight management (1 RCT and 1 pre-post design) ( Ferrante et al, 2018 ;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 17 RCTs ( Willems et al, 2017 ; Mendoza et al, 2017 ; Graetz et al, 2018 ; Ferrante et al, 2018 ; Admiraal et al, 2017 ; Compen et al, 2018 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Greer et al, 2019 ; Ham et al, 2019 ; Ji et al, 2019 ; Kubo et al, 2019 ; Rosen et al, 2018 ; Uhm et al, 2017 ; Urech et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2018 ) and 8 pre-post design studies ( Børøsund et al, 2019 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; McCarroll et al, 2015 ; Pappot et al, 2019 ; Park et al, 2019 ; Pope et al, 2019 ; Trinh et al, 2018 ). Nine studies (5 RCTs and 4 pre-post designs) tested physical activity / rehab / fitness interventions ( Mendoza et al, 2017 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Ji et al, 2019 ; Uhm et al, 2017 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; Park et al, 2019 ; Trinh et al, 2018 ), six studies – CBT interventions (4 RCTs and 2 pre-post designs) ( McCarthy et al, 2018 ; Willems et al, 2017 ; Compen et al, 2018 ; Greer et al, 2019 ; Greer et al, 2019 ; Ham et al, 2019 ; Børøsund et al, 2019 ), three studies - mindfulness/stress management interventions (3 RCTs) ( Kubo et al, 2019 ; Rosen et al, 2018 ; Urech et al, 2018 ), two studies - social support (1 RCT and 1 pre-post design) ( Zhu et al, 2018 ; Pappot et al, 2019 ), two studies - information/psychoeducation (2 RCTs) ( Graetz et al, 2018 ; Admiraal et al, 2017 ), two studies – weight management (1 RCT and 1 pre-post design) ( Ferrante et al, 2018 ;…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (15 RCTs and 7 pre-post designs) found that mHealth interventions were associated with improvement in at least one domain of HRQoL of cancer patients ( Willems et al, 2017 ; Graetz et al, 2018 ; Ferrante et al, 2018 ; Compen et al, 2018 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Greer et al, 2019 ; Greer et al, 2019 ; Ji et al, 2019 ; Kubo et al, 2019 ; Rosen et al, 2018 ; Uhm et al, 2017 ; Urech et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2018 ; Børøsund et al, 2019 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; McCarroll et al, 2015 ; Pappot et al, 2019 ; Park et al, 2019 ; Trinh et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous barriers to in-person participation exist in the normal course of cancer care including travel burden, institutional resources (e.g., space), symptom burden, demanding treatment schedules, and susceptibility to infection in immune-compromised patients [ 10 ]. Prior research on virtual delivery of mind-body programs supports the feasibility and benefits of these services but has focused on mindfulness interventions delivered individually through a website or app [ 11 13 ]. Our virtual classes overcome barriers to in-person delivery while providing a range of services (e.g., fitness, music).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that technologies (e.g., telehealth) may be particularly useful to address issues cancer caregivers experienced during COVID-19; with some research identifying the potential improvement to health and well-being [ 23 25 ]. Technology-based interventions can offer greater accessibility to care for cancer caregivers that can be: (1) delivered remotely without physical contacts between interventionists and the caregivers [ 26 , 27 ], (2) received cost-effectively without the need for transportation [ 24 ], and accessed conveniently with self-paced learning [ 28 , 29 ] of tailored content [ 30 , 31 ]. In addressing the unique challenges cancer caregivers face amidst COVID-19, no research has identified technology-based health solutions for cancer patients that can address these needs, such as care needs, general healthcare needs, information and communication needs, and social support needs (see Table 1 ).…”
Section: Introductionmentioning
confidence: 99%